Phenomenological Perspective of Indonesian Student Resilience Post-Conflict Sudan - Fatimah, Maulida Nurul; Zhohiru, Muh (Jurnal Psikologi Islam dan Budaya, 2025)
This study aims to explore the subjective experiences of Indonesian students in developing resilience following the Sudan conflict. A qualitative phenomenological design was applied involving three male Indonesian students (aged 24) who were evacuated from Sudan and continued their studies in Indonesia. Data were collected through in depth interviews (face to face and online) and analyzed using Interpretative Phenomenological Analysis (IPA). Findings indicate that resilience emerged through three major processes: acceptance, positive meaning-making, and social support. External support from parents, peers, and the Muhammadiyah organization were essential, while internal factors such as optimism, mental endurance, and spirituality reinforced recovery and adaptation. The study demonstrates that resilience functions as a key psychological mechanism that enables students to rebuild educational aspirations and emotional well-being after traumatic conflict experiences.